Volumetric analysis of root canal filling in deciduous teeth after using different canal-drying methods: An In-vitro study - C S Sri Darshini; Preetha Peethambar; Sapna Konde; Manisha Agarwal (Wolters Kluwer Medknow Publications, 2019)
Background: Drying the root canals in pulp therapy is often ignored, but is essential for a successful clinical outcome. The conventional method used for drying root canals is by the use of paper points, but recently, various other methods have also been employed for this purpose. Aim: The purpose of this study was to volumetrically analyze root canal fillings in deciduous teeth, after using different canal-drying methods namely 95% ethanol, CANAL CLEAN (Cerkamed Medical Company), and Endo-Aspirator (Cerkamed Medical Company), and compare with the conventional paper point drying method. Methodology: Access cavities were prepared on eighty extracted primary canines, and irrigation was done with 1% sodium hypochlorite and normal saline while enlarging the canals. The specimens were then scanned using a cone-beam computed tomography (CBCT), and preobturation volume (X) of each tooth was measured. The teeth were then randomly divided into two groups - Group 1 - Zinc oxide eugenol (ZOE) group and Group 2 - Metapex group. Each group was further divided randomly into four subgroups based on the drying agent used - Subgroup A - Control group, Subgroup B - 95% ethanol group, Subgroup C - CANAL CLEAN group, and Subgroup D - Endo-Aspirator group. After obturation, a second CBCT was taken to measure the postobturation volume (Y). The percentage of obturated volume was calculated by the following formula: (postobturation volume/preobturation volume) ×100 ([Y/X] ×100). Statistical Analysis: The obtained data were tabulated and subjected to statistical analysis using one-way ANOVA test and unpaired t-test. Results: A significantly high postobturation volume was seen after using 95% ethanol followed by CANAL CLEAN, Endo-Aspirator, and paper points. On comparing the obturation volumes within Metapex and ZOE groups, Metapex group had significantly high obturation volumes irrespective of the drying method used. Conclusion: 95% ethanol is the best intracanal drying agent as it provides optimum pupal obturation.